Lesson Learned from UI GreenMetric World University Rankings Network Participants during The First Virtual Workshop - Riri Fitri Sari; Jauzak Hussaini Windiatmaja; Sabrina Hikmah Ramadhianti (Universitas Diponegoro, 2021)
UI GreenMetric World University Rankings is a non-profit initiative from the University of Indonesia that ranks universities around the world based on their commitment and actions towards sustainability. During the ranking process, many universities’ performance in UI GreenMetric has progressed. To increase the performance of each university in UI GreenMetric, universities need to share their sustainability achievement and current condition in a forum. These universities can share information about the implementation of sustainability policies in each university through the International Workshop on UI GreenMetric World University Rankings. Due to the ongoing pandemic and our concerns that the event could ease the spread of coronavirus, this event was also being held online. We evaluate the workshop to capture the experience gained in organizing the event. We conclude that online workshops such as IWGM are conductible, although we also understand that every event is unique and new lessons can be learned from each new event